Respuestas
Respuesta dada por:
0
Resolver.
(- 3) + ( +5) = Para quitar el parentesis + por + = +
- 3 + 5 =
2
Respuesta.
2
(- 3) + ( +5) = Para quitar el parentesis + por + = +
- 3 + 5 =
2
Respuesta.
2
Respuesta dada por:
0
Aplicamos regla de signos.
(-) (+) = -
(+)(-) = -
(+)(+) = +
(-)(-) = +
Resolvemos :
(-3) + (+5)
- 3 + 5
2
(-) (+) = -
(+)(-) = -
(+)(+) = +
(-)(-) = +
Resolvemos :
(-3) + (+5)
- 3 + 5
2
Preguntas similares
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años